ANALYSIS ON "THE BRIDGE ENGLISH COMPETENCE", STUDENT TEXTBOOK FOR GRADE IX JUNIOR HIGH SCHOOL, BASED ON SCHOOL BASED CURRICULUM - MURNIATI, SILIH (2010)
This researcher paper is mainly intended to find out whether or not the English textbook used for the ninth year students of Junior High School "The Bridge English Competence" compatible with indicators of the language skill suggested by School Based Curriculum. The researcher applies descriptive qualitative research. In collecting the data, the writer used documentary analysis especially in content analysis as the instrument. The data were analyzed by these steps: (1). Presents indicators of the school level-based curriculum, and the indicators in the textbook, (2). Compares the indicators in the School Based Curriculum with those in the textbook, (3). Then judges whether the English textbook is appropriate with the School Level based Curriculum or not, and drawing conclusions based on the result of analysis. The result of the data analysis shows that the percentage of the compatibility of the language skill indicators developed in the textbook is (72%). It means that the textbook is good at developing language skill suggested by School Based Curriculum. The language skills which are developed in the textbook involve: the compatibility of the listening indicator is (78%) or very good with the indicators of School Based Curriculum, the compatibility of the speaking indicator is (68%) or good with the indicators of school Based Curriculum, the compatibility of the reading indicator is (73%) or good with the indicators of School Based Curriculum, for the writing indicator is (67%) or good, means that the writing indicator is appropriate with the writing skill indicators of the school Based Curriculum. This research implies that the textbook entitled "The Bridge English Competence" is good to support the learning process in all of language skills.